Influence of mulches on rhizosphere microflora, yield and weed competition in okra [Abelmoschus esculentus (L.) Moench] - Faras Bin Muhammed, U.P.; Sindhu, P.V.; Surendra Gopal, K.; George Thomas, C. (Journal of Tropical Agriculture, 2015)
A field experiment was conducted during the summer season of 2014 to study the effect of various mulching materials on rhizosphere microflora, yield and weed competition in okra. Mulching with black polythene sheet recorded the highest yield (15.63 Mg ha-1) of okra. Among organic mulches used, mango leaves and newspaper recorded higher yield of 10.06 and 9.37 Mg ha-1respectively, along with higher microbial population in okra rhizosphere. Mulching had great influence on the population of bacteria, fungi and actinomycetes as compared to unmulched plots. All the treatments with mulches favoured the population of fungi and actinomycetes and crop yield. Pre emergence spraying of pendimethalin @ 1.0 kg ha-1 gave the lowest weed count and weed dry weight. The least weed index was recorded in hand weeding (23.1) followed by mango leaves, pendimethalin and mulching with paper.